Exam ref 70-413 : designing and implementing a server infrastructure / Steve Suehring - Suehring, Steve
Prepare for Exam 70-413—and help demonstrate your real-world mastery of enterprise server design and implementation. Designed for experienced, MCSA-certified professionals ready to advance their status— Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSE level. Optimize your exam-prep by focusing on the expertise needed to: Plan and Deploy a Server Infrastructure Design and Implement Network Infrastructure Services Design and Implement Network Access Services Design and Implement an Active Directory Infrastructure (Logical) Design and Implement an Active Directory Infrastructure (Physical).